DEVELOPING VIDEO OF SET MATERIALS USING BANDICAM AS LEARNING MEDIA AMID PANDEMIC - Siti Khoiriyah; Nihayati Nihayati; Rahmatika Kayyis (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Students have difficulty in understanding Mathematical concepts because the instructional media are difficult to understand. It is necessary to have instructional media that is attractive, comprehensive and supports online learning. Bandicam software offers a chance for teachers to create an interesting instructional video that supports online learning.  Based on the aim, Research and Development (R&D) with a 4-D development is used. The sample was the seventh grade of SMP Muhammadiyah Ambarawa that learned about Set Material.  The results showed that instructional video using Bandicam software was identified as feasible as an online instructional media. The results of the expert's assessment found that the average score from the set material expert was 82.33%, and from the media, the expert was 85.09%. The results of the trial stated that the students’ average using the instructional video was 82.61%. Based on the expert and student's assessment, it can be concluded that instructional video using Bandicam software is suitable as an online instructional media.